An efficient and accurate framework for calculating lattice thermal conductivity of solids: AFLOW—AAPL Automatic Anharmonic Phonon Library. (December 2017) - Plata, Jose; Nath, Pinku; Usanmaz, Demet; Carrete, Jesús; Toher, Cormac; Jong, Maarten; Asta, Mark; Fornari, Marco; Nardelli, Marco; Curtarolo, Stefano
Abstract One of the most accurate approaches for calculating lattice thermal conductivity, $$κ _\ell$$ DMPSID=1, is solving the Boltzmann transport equation starting from third-order anharmonic force constants. In addition to the underlying approximations of ab-initio parameterization, two main challenges are associated with this path: high computational costs and lack of automation in the frameworks using this methodology, which affect the discovery rate of novel materials with ad-hoc properties. Here, the Automatic Anharmonic Phonon Library (AAPL) is presented. It efficiently computes interatomic force constants by making effective use of crystal symmetry analysis, it solves the Boltzmann transport equation to obtain $$κ _\ell$$ DMPSID=2, and allows a fully integrated operation with minimum user intervention, a rational addition to the current high-throughput accelerated materials development framework AFLOW. An "experiment vs. theory" study of the approach is shown, comparing accuracy and speed with respect to other available packages, and for materials characterized by strong electron localization and correlation. Combining AAPL with the pseudo-hybrid functional ACBN0 is possible to improve accuracy without increasing computational requirements. Thermal conductivity: Framework for calculating heat flow in solids A new theoretical framework could provide a more efficient method for calculating a material's thermal conductivity. Understanding how materials conduct heat is crucial for a range of applications, from heat sinks to thermal insulation. Despite its fundamental importance, predicting a material's lattice thermal conductivity is challenging, and often requires experimental data or knowledge of specific properties to be entered during the process. An international team of researchers led by Stefano Curtarolo from Duke University now present a framework that can predict the lattice thermal conductivity of single-crystal and polycrystalline materials using just a single input file, with no further intervention. Called the Automatic Anharmonic Phonon Library, the methods computes certain parameters using symmetry analysis, before solving the Boltzmann transport equation, providing information on both the electronic structure and phonon-dependent properties.